2002
DOI: 10.1889/1.1827836
|View full text |Cite
|
Sign up to set email alerts
|

A study on the chromaticity shifts of blue phosphor for color plasma displays

Abstract: Abstract— The dependency of the chromaticity shifts on the concentration of Eu2+ doped in BaMgAl10O17 (BAM) was investigated under heat‐treatment and vacuum ultraviolet (VUV) irradiation. The Eu2+ ions in BAM show an asymmetrical broad emission band with a maximum at ∼452 nm under excitation of VUV light at room temperature, showing that multiple crystalline cationic sites exist in the host. It was found that the chromaticity shifts greatly decrease with increasing heat‐treatment temperature. Regardless of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…A new Eu 2+ emission peak appears at about 500 nm, along with an even broader tail that extends beyond 600 nm. The peak at B500 nm has been reported before for VUV-damaged BAM doped with 10% Eu [18]. The new features in the emission spectra may come either from newly formed electronic defect centers in the host lattice, or from new Eu 2+ centers.…”
Section: Article In Presssupporting
confidence: 68%
“…A new Eu 2+ emission peak appears at about 500 nm, along with an even broader tail that extends beyond 600 nm. The peak at B500 nm has been reported before for VUV-damaged BAM doped with 10% Eu [18]. The new features in the emission spectra may come either from newly formed electronic defect centers in the host lattice, or from new Eu 2+ centers.…”
Section: Article In Presssupporting
confidence: 68%
“…2 present an asymmetrical broad band with a maximum around 450 nm. This is due to the multiple crystalline sites for Eu 2+ to occupy [8]. Therefore, the distribution of Eu 2+ in different sites will result in different emission spectral features, such as peak position and full-width at halfmaximum (FWHM), which leading to different chromaticity coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…The oxidation of Eu 2+ has been well accepted as the thermal degradation mechanism [3][4][5], but recent studies suggested contrary interpretations such as an altered local environment of Eu 2+ [6] or the intercalation of water in the conduction layer [7]. In addition, the annealing-induced color shift of BAM has been reported [4,8], but its reason is still not explained. Therefore, the thermal degradation mechanism of BAM still remains somewhat mysterious and needs more efforts to study.…”
Section: Introductionmentioning
confidence: 99%
“…This asymmetry is due to the multiple crystalline sites for Eu 2+ to occupy in BaMgAl 10 O 17 host [16]. According to Refs.…”
Section: Luminescent Properties Before Annealingmentioning
confidence: 99%